Quotes, Paraphrases, and Allusions: Text Reuse in Sanskrit Commentaries and How to Encode It - Patrick McAllister (Journal of the Text Encoding Initiative)
The Sanskrit literary genre of commentaries has several characteristics that are a challenge to the structural encoding of its texts. One particular tricky feature is the skillful and sophisticated reuse of text in such commentaries. This article examines practical examples of encoding these types of passages, drawing on the documents of SARIT1 (Search and Retrieval of Indic Texts) and the author’s own encoding projects.